Ultrastructure of Septa in Sclerotinia sclerotiorum - Buddy Dani Kosasih (Institute for Research and Community Services (LPPM) ITB, 1975)
Abstract. An electron microscope study has been done on the structure of septum and its associations of Sclerotinia sclerotiorum (Lib.) de Bary. This septum consists of a cross-wall containing two electron-dense layers separated by an electron-transparent central lamella. The central pore in the cross-wall is partially to completely blocked by cell inclusions called Woronin bodies, which are electron-dense and membrane-bound. Ringkasan. Pengamatan jamur penyebab penyakit tumbuhan, Sclerotinia sclerotiorum (Lib.) de Bary dengan menggunakan mikroskop elektron telah dikerjakan dalam laporan ini, terutama sekali mengenai dinding melintang dari pada hypha dan benda-benda sel lainnya yang selalu berhubungan erat sekali dengan celah di antara dinding melintang, yang disebut